Outcomes of inquiry-based learning in health professions education: A scoping review - Verma, Subhrata; Yacob, Marina S; Kirpalani, Amrit (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Background: Open inquiry-based learning (IBL) that aims to foster higher-level thinking, is defined by students formulating their own questions and learning through exploration. The present study aimed to summarize the breadth of metrics used to evaluate health professions trainees in open IBL curricula.Methods: We conducted a scoping review to identify publications detailing trainee outcomes in open IBL initiatives in health professions education. We queried five databases and included studies which described interventions with five phases of IBL (orientation, conceptualization, investigation, conclusion, and discussion). We completed abstract and full text reviews in duplicate. Data were collated and summarized.Results: From 3030 record, 21 studies were included in the final extraction (k = 0.94), with nine involving physician trainees and twelve involving nursing trainees. Three studies used validated data collection tools to measure student inquiry behavior, and a single study used a validated data collection tool to measure critical thinking abilities. Most studies (n = 11) reported trainee self-reported satisfaction or perceived gain of skills as the primary outcome. All four studies using validated tools reported high scores in inquiry behaviors at the end of the curriculum and results on critical thinking skills were mixed. One study collected serial data, while remaining studies collected pre-post or post-only data.Conclusion: IBL has the potential to cultivate a climate of curiosity among health professions learners. However, studies have relied heavily on subjective outcomes. Limited studies reported standardized measures of inquiry behaviors suggest favorable results. Curriculum innovations using IBL could make use of existing tools to better understand their impact on students’ inquiry-oriented skills.